Cost-utility and budget impact analysis for stopping the inappropriate use of proton pump inhibitors after cessation of NSAID or low-dose acetylsalicylic acid treatment - Chau, Sek Hung; Sluiter, Reinier Luuk; Hugtenburg, Jacqueline Geertruida; Wensing, Michel; Kievit, Wietske; Teichert, Martina (Drugs & aging, 2020)
In accordance with current guidelines, proton pump inhibitors (PPIs) are now generally prescribed as a protective co-medication in patients taking non-steroidal anti-inflammatory drugs (NSAIDs) or low-dose acetylsalicylic acid (LDASA). However, less attention is paid to the corresponding discontinuation of a PPI after cessation of NSAID or LDASA treatment.
Published online: 27 September 2019
Gesehen am 01.04.2020